PKM Pemeriksaan Tekanan Darah Lansia dengan Hipertensi di Dusun Nanggungan Desa Jatirejo Kecamatan Diwek Kabupaten Jombang - Sri Sayekti; Lestari Ekowati; Fissi Tsurayya Nila Yasmin (Yayasan Daarul Huda Kruengmane, 2023)
Hypertension or high blood pressure is a major risk factor for atherosclerotic cardiovascular disease, heart failure, stroke, and kidney failure. Hypertension carries a risk of premature mortality, which increases as systolic and diastolic pressures increase. Prolonged increase in blood pressure damages the blood vessels in the heart, kidneys, brain and eyes. Several studies have shown that people with hypertension are 12 times more likely to have a stroke and 6 times more likely to have a heart attack. Blood pressure checks were carried out on 100 people. The instruments used were a tensimeter and a blood pressure questionnaire sheet. The age of the majority of respondents was at the age of 41-50 years as many as 23 people (23%). Based on the results of an examination of the description of blood pressure on respondents in Nanggungan Hamlet, Jatirejo Village, they are in the Class I Classification of Hypertension (blood pressure 140 – 159 mmHg) with an average age of respondents is 41 – 50 years. After measuring blood pressure, they were given health education about hypertension.